Lysosomal exocytosis releases pathogenic α-synuclein species from neurons in synucleinopathy models - Ying Xue Xie; Nima N. Naseri; Jasmine Fels; Parinati Kharel; Yoonmi Na; Diane Lane; Jacqueline Burré; Manu Sharma (Nature Communications, 2022)
Release of α-synuclein aggregates by neurons instigates spread of pathology in synucleinopathies, but the mechanism remains unclear. Here the authors show that neuronally generated α-synuclein aggregates accumulate within neuronal lysosomes and are released via SNARE-dependent lysosomal exocytosis.